Differences in intragastric pH in diabetic vs. idiopathic gastroparesis: relation to degree of gastric retention - Hasler, William L; Coleski, Radoslav; Chey, William D; Koch, Kenneth L; McCallum, Richard W; Wo, John M; Kuo, Braden; Sitrin, Michael D; Katz, Leonard A; Hwang, Judy; Semler, John R; Parkman, Henry P (American journal of physiology: Gastrointestinal and liver physiology, 2008)
Evidence suggests that distinct mechanisms underlie diabetic and idiopathic gastroparesis. Differences in gastric acid in gastroparesis of different etiologies and varying degrees of gastric stasis are uninvestigated. We tested the hypotheses that 1) gastric pH profiles show differential alteration in diabetic vs. idiopathic gastroparesis and 2) abnormal pH profiles relate to the severity of gastric stasis. Sixty-four healthy control subjects and 44 gastroparesis patients (20 diabetic, 24 idiopathic) swallowed wireless transmitting capsules and then consumed (99m)Tc-sulfur colloid-labeled meals for gastric scintigraphy. Gastric pH from the capsule was recorded every 5 s. Basal pH was higher in diabetic (3.64 +/- 0.41) vs. control subjects (1.90 +/- 0.18) and idiopathic subjects (2.41 +/- 0.42; P < 0.05). Meals evoked initial pH increases that were greater in diabetic (4.98 +/- 0.32) than idiopathic patients (3.89 +/- 0.39; P = 0.03) but not control subjects (4.48 +/- 0.14). pH nadirs prior to gastric capsule evacuation were higher in diabetic patients (1.50 +/- 0.23) than control subjects (0.58 +/- 0.11; P = 0.003). Four-hour gastric retention was similar in diabetic (18.3 +/- 0.5%) and idiopathic (19.4 +/- 0.5%) patients but higher than control subjects (2.2 +/- 0.5%; P < 0.001). Compared with control subjects, those with moderate-severe stasis (>20% retention at 4 h) had higher basal (3.91 +/- 0.55) and nadir pH (2.23 +/- 0.42) values (P < 0.05). In subgroup analyses, both diabetic and idiopathic patients with moderate-severe gastroparesis exhibited increased pH parameters vs. those with mild gastroparesis. In conclusion, diabetic patients with gastroparesis exhibit reduced gastric acid, an effect more pronounced in those with severely delayed gastric emptying. Idiopathic gastroparetic subjects exhibit nearly normal acid profiles, although those with severely delayed emptying show reduced acid vs. those with mild delays. Thus both etiology and degree of gastric stasis determine gastric acidity in gastroparesis.